Analysis of the Use of Wakamono Kotoba on the Nihongo Mantappu Channel Vlog "Hunting Street Food at Dotonbori Osaka!|Waseda Boys Sakura Trip#2" - Tresnasari, Ningrum (CENTRAL ASIA AND THE CAUCASUS, 2022)
Wakamono Kotoba is generally used by Japanese teenagers which is a form of slang variant and is included in certain expressions to convey freedom or as entertainment. This study aims to determine the characteristics of the pattern of formation, changes in the meaning of Wakamono Kotoba, and to help Japanese language learners by using a referential equivalent research method to the sample data studied, namely the nihongo Mantappu vlog entitled Hunting Streest Food in Dotonbori Osaka! Waseda boys Sakura trip #2. The results of this study concluded that there are 3 types of Wakamono Kotoba based on their formation contained in the sample data that has been studied so that the learning process of language learners will be encouraged by their interest in the facts of the origin of the vocabulary they know.